Combined sulfur, carbon and redox budget constraints on genetic models for the Here's Your Chance Pb-Zn deposit, Australia - Dick, Jeffrey; Evans, Katy; Holman, Alex; Leach, D.; Grice, Kliti (Elsevier Science BV, 2014)
The formation of base metal sulfide deposits requires not only a source of metals but also reduced sulfur. If incoming sulfur is present in ore fluids as sulfate, then a source of electrons is needed to drive the reduction of sulfate to sulfide. The oxidation of organic matter can release electrons that provide the reducing capacity, whether it be in low- or high-temperature settings that are conducive to biological or thermochemical sulfate reduction (BSR or TSR). The amounts of organic matter reacted and sulfide minerals formed can be estimated by mass balance calculations. In this study, an integrated mass balance expression is formulated that takes into account the sulfide mineral content and organic carbon content and H/C ratios of mineralised and non-mineralised rocks. Model calculations based on carbon, sulfur and redox budget balances suggest that the extent of oxidation of the organic matter present at the Here’s Your Chance (HYC) Pb–Zn deposit is insufficient for reduction of the required quantity of sulfate. The results imply that externally derived reducing capacity and/or reduced sulfur is required to form the metal resource. Possible sources include hydrocarbon-rich fluids from deeper parts of the sedimentary sequence or formation of sulfide and organic matter as products of BSR during sedimentation/early diagenesis. However, the observed oxidation of organic matter associated with the deposit suggests that at least some reducing capacity is locally derived. Therefore, our calculations are consistent with genetic models for HYC that have multiple sources of redox budget for sulfate reduction.